Analisis Kinerja Rantai Pasok Ikan Nila Pada Bandar Sriandoyo Kecamatan Tugumulyo Kabupaten Musi Rawas: Pendekatan Food Supply Chain Networks (FCSN) - setiadi Setiadi (Politeknik Negeri Lampung, 2017)
ABSTRACTÂ Supply chain network of tilapia products, which is run by Bandar Sriandoyo as a business unit engaged in the marketing and distribution of tilapia fish in partnership with tilapia fish farmers in Tugumulyo District Musi Rawas Regency, has a goal to meet some of the needs of tilapia products for consumers in region of South Sumatera Province. The model of supply chain of indigo fish in Musi Rawas Regency is discussed descriptively by using development method following Food Supply Chain Networks (FSCN) process framework. The results showed that the supply chain of tilapia fish at Bandar Sriandoyo in Tugumulyo District of Musi Rawas Regency based on FSCN approach involves supply chain members consisting of partner farmers, Bandar Sriandoyo, bakul (wholesalers), and retailers. The flow patterns of goods, financial flows, and the flow of information have generally been relatively good. In particular, the dynamic flow of information becomes an important factor in the running of business processes and collaborative planning, as well as building trust among the members of the indigo fish supply chain.